IDENTIFYING BOUND MORPHEME IN THE NOVEL “THE ALCHEMIST” BY PAULO COELHO - Alifa Nadya Rifani; Lilia Indriani (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This article highlights the analysis of bound morpheme in the novel “The Alchemist” by Paulo Coelho. The bound morpheme is the element that explores the field of morphology for daily language users. There is no linguistic meaning at bound morpheme. Nevertheless, they have linguistic meaning when they are connected to a root word. Bound morpheme frequently comes out as affixes in the English language. The main issue in this study is to analyze the bound morpheme found in the novel “The Alchemist”. This article is related to linguistics and the field of sociolinguistics. This paper is solely based on a qualitative research approach. The writer used the words in the novel as the data and focused on analyzing bound morphemes. Two categories of bound morpheme that be analyzed are prefixes and suffixes used in the novel “The Alchemist”. As a result, Paulo Coelho used the prefixes and suffixes based on their role in the root word.